EVALUATION OF THE BODILY-KINESTHETIC INTELLIGENCE MODEL IN PHYSICAL EDUCATION TEACHING IN INDONESIA PRIMARY SCHOOL - Suhadi Suhadi; Soegiyanto Soegiyanto; Hari Amirruloh Rahman; Sulaiman Sulaiman (LPMPP Universitas Negeri Yogyakarta, 2020)
Bodily-kinesthetic intelligence model refers to a person's potential to body fact system via hand and physique movement, control, and expression. This model is still rarely known in Indonesian primary school. The aim of this research was to determine the current bodily-kinesthetic intelligence model in physical education teaching for primary schoolers. Descriptive research was conducted with a qualitative and quantitative approach. The sample of this study was physical education teachers and primary school students. Literature review of the documents, questionnaire, observation, video recordings, photography and diary were used to explore the level of the student mind and fitness body. The result showed that the current Bodily-kinesthetic intelligence model in Physical Education Teaching did not allow the appearance of increasing the maximum of their physical and mental abilities. In conclusion, this study gives the assessment model of student human kinetic in order to fix the current issue of competence evaluation. Physical education teachers need to improve their teaching methods to allow students to reach physical and mental performance.